IHTIKAR: PERILAKU MENIMBUN DALAM KAJIAN MUAMALAH - taufiq taufiq; Razali Razali (JURIS (Jurnal Ilmiah Syariah), 2020)
Fiqh termed hoarding goods with the word ihtikar, various definitions were given by the jurists about Ihtikar. In the context of conventional economic Ihtikar synonymous with monopoly. Prohibition of ihtikar in Islam in order to realize justice in the market between producers and consumers. There are three categories of ihtikar law in fiqh muamalah, which are haram, makhruh and may. illat ihtikar incompetence is on goods that are needed by many people and becomes expensive if it is controlled by one party. Islam provides space for the government to intervene in the market so that the circulation of people's needs in the market takes place normally. Even in the study of siyasah muamalah, the jurists advocated the formation of the Hisbah to control the market mechanism in order to realize economic justice.